2006
DOI: 10.1021/jp057073v
|View full text |Cite
|
Sign up to set email alerts
|

Quantitating the Dynamics of NBD Hexanoic Acid in Homogeneous Solution and in Solutions Containing Unilamellar Vesicles

Abstract: We report here on the motional and fluorescence lifetime dynamics of the chromophore NBDHA (6-(N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino)hexanoic acid) in neat solvents and in aqueous solutions containing unilamellar vesicles of varying composition. We measure the transient response of this chromophore by time-correlated single-photon counting, using one- and two-photon excitation to resolve the Cartesian components of the rotational diffusion constant, D. Our experimental data for NBDHA in selected solvents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 34 publications
(103 reference statements)
0
20
0
Order By: Relevance
“…The fluorescence lifetime of NBD depends not only on the polarity of the environment but also on the hydrogen-bonding donor capacity of the solvent. Previous studies have shown that when a NBD fluorophore is exposed to different protic and aprotic solvents, the fluorescence lifetime ranges from ϳ1 ns for purely water to Ͼ10 ns in ethyl acetate (33,34). A fluorescent lifetime of around 7 ns is observed when NBD is dissolved in butanol, a value that corresponds to the fluorescence lifetimes observed for positions within or close to the hydrophobic constriction ring, which consists mainly of isoleucines.…”
Section: Discussionmentioning
confidence: 90%
“…The fluorescence lifetime of NBD depends not only on the polarity of the environment but also on the hydrogen-bonding donor capacity of the solvent. Previous studies have shown that when a NBD fluorophore is exposed to different protic and aprotic solvents, the fluorescence lifetime ranges from ϳ1 ns for purely water to Ͼ10 ns in ethyl acetate (33,34). A fluorescent lifetime of around 7 ns is observed when NBD is dissolved in butanol, a value that corresponds to the fluorescence lifetimes observed for positions within or close to the hydrophobic constriction ring, which consists mainly of isoleucines.…”
Section: Discussionmentioning
confidence: 90%
“…[7] This is the case for NBD, which is treated as a prolate rotor with a mono-exponential anisotropy decay. [10] For tryptophan, however, the highest observed anisotropy is 0.3. [7] …”
Section: Resultsmentioning
confidence: 97%
“…Fluorescence anisotropy ( r ) can be affected by a number of parameters as shown in Equation (2) where τ is the fluorescence lifetime, η is solvent viscosity, ${\cal R}$ is the universal gas constant, T is temperature, V is the effective hydrodynamic volume of the fluorophore (related to its rotational and translational diffusion coefficients) and r 0 is the maximum possible anisotropy for the molecule (usually close to 0.4 for randomly distributed geometries) 7. This is the case for NBD, which is treated as a prolate rotor with a mono‐exponential anisotropy decay 10. For tryptophan, however, the highest observed anisotropy is 0.3 7…”
Section: Resultsmentioning
confidence: 99%
“…It is the functional form and the time constant(s) associated with the decay of R ( t ) that are related to the local environment of the reorienting molecule. Chuang and Eisenthal developed a model for fluorescence anisotropy decay that provides a means of interpreting anisotropy decay functions containing up to five exponential components. ,, Despite this potential for complexity, one or two decays are the functional forms observed most commonly. For the excitation and emission transition moments oriented parallel to one another, along the long axis in the chromophore π-system plane, reorientation of the chromophore as a prolate rotor ( D x > D y = D z ) gives rise to a single exponential decay of R ( t ) (eq ), and reorientation as an oblate rotor ( D z > D x = D y ) produces a two-component R ( t ) function, as described by eq .…”
Section: Resultsmentioning
confidence: 99%